STRATEGI PK IPNU-IPPNU DALAM MENINGKATKAN KARAKTER ANGGOTA MELALUI BUDAYA RELIGIUS DI UNIVERSITAS - Sihaloho, Atika Putri Pratiwi; Maulana Nur Kholis; Fahrul Ashari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of religious culture in an organization is an important strategy for improving member character through providing understanding, motivation, habituation, and supervision based on Islamic values. This study aims to: (1) analyze the implementation of the IPNU-IPPNU Student Leadership Council (PK IPNU-IPPNU) strategy in improving member character through religious culture at KH. Abdul Chalim University, Pacet, Mojokerto; (2) analyze the supporting factors, obstacles, and solutions in implementing this strategy; and (3) analyze the results achieved from implementing this strategy. This study used a qualitative approach with a case study. Data were collected through interviews, observations, and documentation involving the supervisor, chairperson, the Da'wah Department, and members of the IPNU-IPPNU Student Leadership Council (PK IPNU-IPPNU) at KH. Abdul Chalim University, Pacet, Mojokerto. The results indicate that the strategies implemented include personal approaches, interpersonal approaches, exemplary leadership from the management, internalization of Nahdlatul Ulama (NU) and Ahlussunnah wal Jama'ah (Aswaja) values, and the habituation of religious activities. Supporting factors for strategy implementation include personal factors, the environment, and facilities and infrastructure. Meanwhile, inhibiting factors include personal aspects, time constraints, and financial constraints. Solutions implemented include increasing member understanding, implementing an inclusive approach, optimizing time management, fostering a sense of belonging to the organization, and implementing a monthly cash program. The implementation of these strategies has been proven to improve member character, including religiousness, discipline, responsibility, tolerance, loyalty, patriotism, social awareness, a love of reading, communication, and mutual respect. Thus, religious culture serves as an effective tool for the sustainable development of organizational members' character.